Benchmarking Single Image Dehazing and Beyond - Li, Boyi; Ren, Wenqi; Fu, Dengpan; Tao, Dacheng; Feng, Dan; Zeng, Wenjun; Wang, Zhangyang (IEEE Transactions on Image Processing, 2019)
In this paper, we present a comprehensive study and evaluation of existing single image dehazing algorithms, using a new large-scale benchmark consisting of both synthetic and real-world hazy images, called REalistic Single Image DEhazing (RESIDE). RESIDE highlights diverse data sources and image contents, and is divided into five subsets, each serving different training or evaluation purpose]s. We further provide a rich variety of criteria for dehazing algorithm evaluation, ranging from full-reference metrics, to no-reference metrics, to subjective evaluation and the novel task-driven evaluation. Experiments on RESIDE shed light on the comparisons and limitations of state-of-the-art dehazing algorithms, and suggest promising future directions.